IPO Timing, Buyout Sponsors’ Exit Strategies, and Firm Performance of RLBOs - Cao, Jerry X. (Journal of Financial and Quantitative Analysis, 2011)
Abstract This paper studies the impact of buyout sponsors’ initial public offering (IPO) timing on the leveraged buyout (LBO) restructuring process and subsequent exit strategies. I find that LBO duration is negatively related to hot IPO market conditions. Further, following IPOs, reverse leveraged buyouts (RLBOs) with shorter LBO duration experience greater deterioration of performance and higher probability of bankruptcy. This suggests that sponsors’ efforts to enhance operating efficiency succumb to market timing. IPO timing does not affect sponsors’ exit strategies and monitoring post IPO. Sponsors keep an active long-run presence with more reputable sponsors who are more likely to exit by facilitating takeovers.